The Role of Village Heads in Resolving Minor Criminal Cases (Study of Resolving Minor Criminal Cases in Trosono Village with a Restorative Justice Approach): Peran Kepala Desa Dalam Penyelesaian Kasus Pidana Ringan (Study Penyelesaian Kasus Pidana Ringan di desa Trosono dengan Pendekatan Restorasi Justice) - Anshori; Sutiyono; Ependi (Al-Jinayah : Jurnal Hukum Pidana Islam, 2024)
Abstract This study aims to analyze the role of village heads in resolving minor criminal cases through a restorative justice approach in Trosono Village. This empirical juridical research focuses on how village heads, as local leaders, mediate conflicts, prioritize deliberation, and maintain social harmony. Data were collected through in-depth interviews, observations, and document reviews, with qualitative-descriptive analysis methods. The findings reveal that the village head plays a central role in facilitating dialogue between disputing parties to reach fair agreements without resorting to formal legal processes. This restorative approach proves effective in resolving minor criminal cases, such as disputes among residents, petty theft, and other incidents that do not require court intervention. Supporting factors for this approach include community trust in the village head, a culture of deliberation, and the support of village officials. However, the main challenges include the village head's limited legal authority and potential external pressures. In conclusion, the restorative justice approach implemented by the village head in Trosono Village has the potential to serve as an effective model for resolving minor criminal disputes at the local level, provided it is supported by clear regulations and synergy with formal law enforcement authorities. Keywords: village head, restorative justice, minor criminal resolution, empirical juridical, Trosono Village.